2001
DOI: 10.1038/35055027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of XAF1 as an antagonist of XIAP anti-Caspase activity

Abstract: The inhibitors of apoptosis (IAPs) suppress apoptosis through the inhibition of the caspase cascade and thus are key proteins in the control of cell death. Here we have isolated the protein XIAP-associated factor 1 (XAF1) on the basis of its ability to bind XIAP, a member of the IAP family. XIAP suppresses caspase activation and cell death in vitro, and XAF1 antagonizes these XIAP activities. Expression of XAF1 triggers a redistribution of XIAP from the cytosol to the nucleus. XAF1 is ubiquitously expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
413
4
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(433 citation statements)
references
References 26 publications
13
413
4
3
Order By: Relevance
“…Real-time RT-PCR (Table 1) and immunoblotting (data not shown) also identified cellspecific induction of XAF1 by IFNs, markedly in SK-MEL-28 but less in SK-MEL-3. XAF1 interacts with an inhibitor of apoptosis (XIAP) that may function as a competitive inhibitor of caspases to play a critical role in TRAIL-induced apoptosis (Deveraux et al, 1997;Liston et al, 2001;Leaman et al, 2002;Chawla-Sarkar et al, 2004). XAF1 has been silenced by DNA methylation in gastric cancer and is frequently reduced in expression in melanoma (Byun et al, 2003;Ng et al, 2004;Reu et al, 2006a).…”
Section: Role Of Trail In Sensitization To Ifns By 5-azadcmentioning
confidence: 99%
“…Real-time RT-PCR (Table 1) and immunoblotting (data not shown) also identified cellspecific induction of XAF1 by IFNs, markedly in SK-MEL-28 but less in SK-MEL-3. XAF1 interacts with an inhibitor of apoptosis (XIAP) that may function as a competitive inhibitor of caspases to play a critical role in TRAIL-induced apoptosis (Deveraux et al, 1997;Liston et al, 2001;Leaman et al, 2002;Chawla-Sarkar et al, 2004). XAF1 has been silenced by DNA methylation in gastric cancer and is frequently reduced in expression in melanoma (Byun et al, 2003;Ng et al, 2004;Reu et al, 2006a).…”
Section: Role Of Trail In Sensitization To Ifns By 5-azadcmentioning
confidence: 99%
“…8 To explore whether XAF1 could sensitize tumor cells to ZD55-triggered death, SW620, A549, NHLF and HSMC were infected with Ad-XAF1, ZD55-EGFP, ZD55-XAF1 or ONYX-015 at various MOIs as indicated. Cells were stained with crystal violet 7 days later.…”
Section: Potent Cytopathic Effect Induced By Zd55-xaf1mentioning
confidence: 99%
“…Overexpression of XAF1 does not appear to induce apoptosis, 8 while previous studies have shown that overexpression of XAF1 could sensitize cancer cells to the proapoptotic effects of etoposide and tumour-necrosis factor-related apoptosis-inducing ligand (TRAIL). 8,14 Recently, it was reported that XAF1 can cooperate with tumor necrosis factor a (TNFa) in the induction of apoptosis.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations